2017
DOI: 10.1038/s41598-017-07356-9
|View full text |Cite|
|
Sign up to set email alerts
|

Suppression of Transposable Elements in Leukemic Stem Cells

Abstract: Genomic transposable elements (TEs) comprise nearly half of the human genome. The expression of TEs is considered potentially hazardous, as it can lead to insertional mutagenesis and genomic instability. However, recent studies have revealed that TEs are involved in immune-mediated cell clearance. Hypomethylating agents can increase the expression of TEs in cancer cells, inducing ‘viral mimicry’, causing interferon signalling and cancer cell killing. To investigate the role of TEs in the pathogenesis of acute … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 56 publications
4
32
0
Order By: Relevance
“…Nevertheless, it is the type of autophagy cargo, which determines the outcome in terms of longevity and aging. This study is in lieu with the observations in AML patients, where ERV regulation correlates with Lamp2, RNautophagy marker [6]. Senolytic drugs under development targets these surveillance resistant senescent cells.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Nevertheless, it is the type of autophagy cargo, which determines the outcome in terms of longevity and aging. This study is in lieu with the observations in AML patients, where ERV regulation correlates with Lamp2, RNautophagy marker [6]. Senolytic drugs under development targets these surveillance resistant senescent cells.…”
Section: Resultsmentioning
confidence: 89%
“…ERV suppression as a potential mechanism in modulating immunogenicity regarding AML development [6].…”
Section: Insights In Biomedicine Issn 2572-5610mentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies describe their role in promoting cancer cell death via activating immune pathways 7,8 . In this context, we recently showed that leukemic stem cells in AML, which are the most resilient to treatment, have suppressed TE expression 21 . A recent study also reported that TE is suppressed in chemotherapy resistant cancer cells 35 This is the first study demonstrating the utility of TE expression signature in predicting prognosis in cancer.…”
Section: Our Findings and Previous Work Suggests That Tp53 Is A Regulmentioning
confidence: 99%
“…TP53 mutation was associated with 6809 AE-non-TE and 40 AE-TE (BH q.value ≤0.05, minimum absolute log-fold-change 0.2). Of the 6809 TP53 mutation specific AE-non-TE, 3918 were clustered into 7 modules with sufficient connectivity metrics as previously described 21 . The 40 AE-TE were correlated to the principle component (PC) 1 of each 7 modules in the TP53 specific-network.…”
Section: Transcript Network Analysis In Tp53 Mutated Aml Exhibits Unimentioning
confidence: 99%